A Practical Method for the Evaluation of Societal Risk in the Context of the International Maritime Organization's Safety Level Approach. (21st January 2018) - Sun, Molin; Zheng, Zhongyi; Gang, Longhui
Abstract : The Safety Level Approach (SLA) is a structured application of risk-based methodologies for the International Maritime Organization's (IMO's) rule-making process. When the SLA is applied, safety goals have to be provided. In order to set appropriate levels for safety goals, it is necessary to measure the tolerance degree of the current safety level. Based on the consistency with individual risk criteria and the principle of continuous improvement, this paper proposes an approach to establish the societal risk criteria, which can be used for setting safety goals in the context of the IMO's SLA. Furthermore, by defining dynamic factors to express risk aversion, a method for tolerance measurement of the current societal risk is developed. Finally, a case study into the societal risk evaluation of cruise ships and Roll-On Roll-Off (RO-RO) passenger ships is conducted.